Flow Cytometric Monitoring for Residual Disease in B Lymphoblastic Leukemia Post T Cell Engaging Targeted Therapies. Issue 1 (13th September 2018) - Cherian, Sindhu; Stetler‐Stevenson, Maryalice
Abstract: The use of targeted therapy is growing in the setting of hematopoietic neoplasms. Flow cytometry is a cornerstone of residual disease monitoring post therapy in this group of malignancies. Often, there is overlap between antigens targeted by immunotherapies and gating reagents utilized for population identification by flow cytometry. Such overlap can render a previously excellent gating reagent inadequate for disease detection. Recently, several anti–CD19 T cell–engaging immunotherapeutic agents and an anti‐CD22 immunotoxin have been FDA approved for use in B lymphoblastic leukemia (B‐LL), with an anti–CD22 T cell–engaging agent in development. In the setting of such targeted therapies, CD19 and CD22 expression may be altered, compromising the use of these reagents for identification of abnormal blasts. We describe herein a strategy for flow cytometric monitoring for residual disease in patients with B‐LL post T cell–engaging anti‐CD19 and anti‐CD22 therapies. © 2018 by John Wiley & Sons, Inc.